Developing therapeutic monoclonal antibodies (mAbs) and antibody-based products 1 - Kayser, Veysel (Henry Stewart Talks, 2022)
Biologics, Monoclonal antibodies (mAbs) history and structure, Manufacturing monoclonal antibodies, Marketed therapeutic monoclonal antibodies, Antibody-Drug Conjugates (ADC), Bispecifics, Vectors & mAb expression, Post translational modifications, Glycosylation